Social Media’s Impact on Political Engagement: PSI Convention Live Stream - Komarudin, Ujang; Panjaitan, Sunardi; Hamid, Abdul (LifeSciFi, 2023)
The presence of the internet and social media has fundamentally changed various human activities, including politics. This study investigates the political engagement strategies of the Partai Solidaritas Indonesia (PSI) through the utilization of social media, with a specific focus on the live streaming program of regional candidate conventions on the YouTube platform. The research examines the impact of PSI’s social media initiatives, aiming to involve the public in the selection of regional leaders in Tangerang Selatan and Surabaya. Using a qualitative descriptive approach, the study analyzes public responses to PSI’s YouTube videos and comments, considering factors such as viewership and engagement. Despite the significant potential for online engagement due to Indonesia’s extensive internet user base, PSI’s failure to formulate a compelling narrative and provide mechanisms for active public participation resulted in limited political engagement. The study reveals that while the convention program aimed to draw media attention and project transparency, it fell short of fostering robust political engagement, emphasizing the need for more inclusive and innovative approaches to political communication in the digital age.